2009
DOI: 10.2169/internalmedicine.48.1662
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy during Acute Adrenal Crisis due to Isolated Adrenocorticotropin Deficiency

Abstract: We report a 69-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Similar to these six cases, intensive stress induced by adrenal insufficiency caused reversible cardiomyopathy in our patient, although the detailed mechanism of left ventricular dysfunction in Takotsubo cardiomyopathy remains unknown [10–17]. According to the report by Ukita et al [8], they listed all cases of Takotsubo cardiomyopathy with isolated ACTH deficiency [57]. Comparing those cases, we found that all cases including ours were female patients although we could not figure out the meanings of the sex difference.…”
Section: Discussionsupporting
confidence: 75%
“…Similar to these six cases, intensive stress induced by adrenal insufficiency caused reversible cardiomyopathy in our patient, although the detailed mechanism of left ventricular dysfunction in Takotsubo cardiomyopathy remains unknown [10–17]. According to the report by Ukita et al [8], they listed all cases of Takotsubo cardiomyopathy with isolated ACTH deficiency [57]. Comparing those cases, we found that all cases including ours were female patients although we could not figure out the meanings of the sex difference.…”
Section: Discussionsupporting
confidence: 75%
“…However, takotsubo cardiomyopathy is very rare in patients with hypopituitarism. In the literature, few takotsubo cardiomyopathy cases have so far presented with adrenal failure (24)(25)(26)(27)(28). Our patient suffered from takotsubo cardiomyopathy seven days after the hydrocortisone replacement therapy.…”
Section: Discussionmentioning
confidence: 75%
“… 2 , 3 Wide varieties of presenting symptoms were reported, including depressive disorder, 4 lower extremities’ motion abnormality, 5 and stress-induced cardiomyopathy. 6 , 7 Compared with primary adrenocortical insufficiency, which has clinical presentations, skin pigmentation, and electrolyte abnormalities including hyponatremia and hyperkalemia, the symptoms and physical findings of secondary adrenocortical insufficiency are nonspecific and difficult to diagnose. Hypercalcemia was reported in 5.5% of primary adrenocortical insufficiency.…”
Section: Discussionmentioning
confidence: 99%